2021
DOI: 10.1080/17461391.2021.1897166
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, screen time and the COVID‐19 school closures in Europe – An observational study in 10 countries

Abstract: To date, few data on how the COVID-19 pandemic and restrictions affected children's physical activity in Europe have been published. This study examined the prevalence and correlates of physical activity and screen time from a large sample of European children during the COVID-19 pandemic to inform strategies and provide adequate mitigation measures. An online survey was conducted using convenience sampling from 15 May to 22 June, 2020. Parents were eligible if they resided in one of the survey countries and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
108
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 44 publications
12
108
0
3
Order By: Relevance
“…One study reported that families with food insecurity increased the quantity of high-calorie foods, increased the disposability of non-perishable processed foods in their homes and exerted greater pressure to children to eat [ 27 ]. Physical activity was also decreased; with recreational areas, parks and sports clubs closed, there has been further reductions in physical activity in children and adolescents [ 28 ] and our data agree with this phenomenon.…”
Section: Discussionsupporting
confidence: 86%
“…One study reported that families with food insecurity increased the quantity of high-calorie foods, increased the disposability of non-perishable processed foods in their homes and exerted greater pressure to children to eat [ 27 ]. Physical activity was also decreased; with recreational areas, parks and sports clubs closed, there has been further reductions in physical activity in children and adolescents [ 28 ] and our data agree with this phenomenon.…”
Section: Discussionsupporting
confidence: 86%
“…An area that has been affected within families is screen time (ST) [ 8 , 9 ]. The use of screens has increased for children as many schools nationwide shifted from conducting classes in person to conducting them remotely.…”
Section: Introductionmentioning
confidence: 99%
“…Despite restrictions allowing 60 minutes of exercise in a local area, nearly 30% of children report not leaving the house on a typical lockdown day 8. With parks, recreational areas, and sports clubs closed and screen time increased, there has been further reduction in physical activity in young people; this is more pronounced among ethnic minority communities 89…”
mentioning
confidence: 99%